IMPLEMENTASI PROYEK PENGUATAN PROFIL PELAJAR PANCASILA UNTUK MENINGKATKAN KARAKTER GOTONG ROYONG PESERTA DIDIK DI SMPN 32 SURABAYA - Lilis Sugandha; Listyaningsih (Kajian Moral dan Kewarganegaraan, 2025)
This study aims to (1) describe the implementation of the Pancasila Student Profile Strengthening Project (P5) with an entrepreneurship theme in forming the mutual cooperation character of students, (2) identify obstacles in its implementation, and (3) reveal the solutions applied at SMPN 32 Surabaya. The research approach used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The research informants consisted of the principal, P5 coordinator, teachers, and students. Data analysis used the Miles and Huberman model, including data reduction, data presentation, and drawing conclusions. The theory used is Thomas Lickona's character education theory, which includes three dimensions, moral knowing, moral feeling, and moral action. The results of the study show that. (1) the implementation of P5 with an entrepreneurship theme has been integrated into group-based activities such as product creation and work presentation, which fosters an attitude of cooperation, responsibility, and positive interaction between students. (2) Obstacles that arise include lack of active participation, unequal group division, and limited facilities. (3) School solutions implement strategies such as forming balanced groups, teacher mentoring, monitoring through journals, and parental involvement. With these strategies, the implementation of P5 is able to strengthen social and collaborative skills, as well as foster a character of mutual cooperation in students as part of the Pancasila student profile.